Research trend on Nuclear Energy from 2008 to 2018: A Bibliometric Analysis - Obregon, Luis; Orozco, Cristhian; Camargo, Josué; Duarte, Jorge; Valencia, Guillermo (International Journal of Energy Economics and Policy, 2019)
This paper presents a bibliometric study of the nuclear energy research output from 2008 to 2018, by mean of the Web of Science (WoS) database. From the 2545 papers published in the period studied, bibliometric indicators were calculated to identify the tendency of this energy source, such as the number of publications by countries, institutions, authors, main keywords reported and the identification of the most cited articles. The results shown the scientific paper as the document type with a more significant number of publications from the total considered (83.4%), and the country with the highest h-index value was the United States, which is also the country with the highest production of articles with a total of (643), followed by China and Germany. An increase in the research outlet was presented in USA (213%) and Germany (182 %) from 2013 to 2017, which is close with the number amount of publication developed by these countries under the figure of international collaboration. Also, the Chinese Academy of Science was the institution with the highest number of publications (79), and the top institution with publications under international network. The results allow to identify the main stakeholders in the nuclear energy research output and determine projections and tendencies on new and complementary topics in this field of study. Keywords: research trend, nuclear energy, bibliometric study, collaboration network, h-index. JEL Classification: Q42 DOI: https://doi.org/10.32479/ijeep.8515